Relative age in Brazilian swimmers and para swimmers - Karla de Jesus; Geovani Messias da Silva; Vitória Miranda dos Santos; Kelly de Jesus; Alexandre Igor Araripe Medeiros (Revista Brasileira de Cineantropometria e Desempenho Humano)
This study aimed to analyze the relationships between swimming competitive events, functional classification and relative age and to detect if the relative age affects performance in Brazilian swimmers and para swimmers. Data were retrieved from public databases and birth dates were classified in four quartiles (Q1 = January-March; Q2 = April-June; Q3 = July-September; Q4 = October-December). Descriptive statistics, Chi-square tests and ANOVA were used. The 50 m freestyle is the competitive event with 2349 swimmers, followed by 100 m (n = 1817) and 200 m freestyle (n = 905), and 200 m butterfly with 42 swimmers. Para swimmers are mainly distributed to S14, S6 and S5 functional classes (n = 140, 87 and 45), and individual medley events were less represented at SM3, SM9 and SM11 (n = 1 swimmer). Most of swimming events (86.36%) and para swimming functional classes (51.43%) are represented by swimmers and para swimmers born in the first and second quartiles. Moderate associations between functional classification and relative age were observed (p < 0.0001, Cramer’s V = 0.277). No effects of relative age on swimmers and para swimmers’ performance were noticed (p > 0.05). The great functional class seems to be related to great para swimmers’ relative age. Quartiles distribution shows the advantage of being born in the first months of the year to be registered among the most talented Brazilian swimmers and para swimmers.